Xanthine oxidase and the fetal cardiovascular defence to hypoxia in late gestation ovine pregnancy. (13th December 2013) - Kane, Andrew D.; Hansell, Jeremy A.; Herrera, Emilio A.; Allison, Beth J.; Niu, Youguo; Brain, Kirsty L.; Kaandorp, Joepe J.; Derks, Jan B.; Giussani, Dino A.
Abstract : Key points: Periods of impaired oxygenation or acute hypoxia in the fetus can be common during labour and how the fetus withstands these challenges is of interest. During hypoxia, the fetus shunts blood flow away from peripheral and towards essential vascular beds: the so called brain‐sparing effect. Part of the peripheral vasoconstriction is driven by reactive oxygen species (ROS) that inactivate nitric oxide (NO), thereby limiting its vasodilator action. Here, we investigate the source of ROS generation contributing to fetal peripheral vasoconstriction during hypoxia, and show that xanthine oxidase (XO) is fundamentally involved. Fetal exposure to the XO inhibitor allopurinol markedly diminished the peripheral vasoconstriction during hypoxia via NO‐dependent mechanisms. The data increase our understanding of the physiological control of fetal cardiovascular function during stress. The findings are also of significant clinical relevance as allopurinol is being administered to pregnant women in clinical obstetric trials. Abstract: Hypoxia is a common challenge to the fetus, promoting a physiological defence to redistribute blood flow towards the brain and away from peripheral circulations. During acute hypoxia, reactive oxygen species (ROS) interact with nitric oxide (NO) to provide an oxidant tone. This contributes to the mechanisms redistributing the fetal cardiac output, although the source of ROS is unknown. Here, we investigated whether ROS derived from xanthine oxidase (XO) contribute to the fetal peripheral vasoconstrictor response to hypoxia via interaction with NO‐dependent mechanisms. Pregnant ewes and their fetuses were surgically prepared for long‐term recording at 118 days of gestation (term approximately 145 days). After 5 days of recovery, mothers were infusedi.v . for 30 min with either vehicle ( n  = 11), low dose (30 mg kg −1, n  = 5) or high dose (150 mg kg −1, n  = 9) allopurinol, or high dose allopurinol with fetal NO blockade ( n  = 6). Following allopurinol treatment, fetal hypoxia was induced by reducing maternal inspired O2 such that fetal basal P aO 2 decreased approximately by 50% for 30 min. Allopurinol inhibited the increase in fetal plasma uric acid and suppressed the fetal femoral vasoconstrictor, glycaemic and lactate acidaemic responses during hypoxia (all P  < 0.05), effects that were restored to control levels with fetal NO blockade. The data provide evidence for the activation of fetal XO in vivo during hypoxia and for XO‐derived ROS in contributing to the fetal peripheral vasoconstriction, part of the fetal defence to hypoxia. The data are of significance to the understanding of the physiological control of the fetal cardiovascular system during hypoxic stress. The findings are also of clinical relevance in the context of obstetric trials in which allopurinol is being administered to pregnant women when the fetus shows signs of hypoxic distress.